A Case of Coincidental Free Floating Thrombus in the Vertebral Artery in a Patient Presenting with an Anterior Circulation Stroke and Literature Review - Hosam Al-Jehani; May Adel Alhamid; Yousef Alkhalaf; Faisal Alabbas (Neurointervention, 2020)
Free-floating thrombus (FFT) is a rare condition with unknown etiology as described by many case reports presented in previous literature. The patients usually present symptomatically while the other few patients remain asymptomatic and are usually discovered incidentally on computed tomography angiography (CTA). Most of the cases reported in the literature are of FFT in the internal carotid artery. We present a 59-year-old female as a case of FFT in the vertebral artery which was coincidently discovered on CTA in a patient initially presenting with an anterior circulation stroke. This case highlights the importance of early contrast-based vascular imaging in patients presenting with large vessel strokes that are cardioembolic in nature and the unique utilization of a direct aspiration first pass technique (ADAPT) for revascularization. Included herein an extensive review of the literature about the decision making in patients with FFT and a devised proposed practical approach to this entity.